Implications of Establishing Village-Owned Enterprises After Law Number 11 of 2020 concerning Job Creation (Case Study of Bumdes in Ngawi Regency) - Oktima Dwi Rahmawati (al-Afkar, Journal For Islamic Studies, 2025)
The enactment of Law Number 11 of 2020 concerning Job Creation and the issuance of Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises. Provide a slight change of view regarding Village Owned Enterprises (BUM Desa). Clearly describes the change from a non-legal entity to a legal entity, and to obtain the status of a Village BUM legal entity, the Village Government must register BUM Desa electronically to the Minister through the Village Information system which has been integrated with the Legal Entity Administration System at the ministry. Which organizes government affairs in the field of law and human rights. The regulation explains that Village-Owned Enterprises have the status of a legal entity but their establishment does not use a notary deed. Only by electronic registration from the Ministry of Law and Human Rights. Therefore, the author wants to analyze the implications of the establishment of BUM Desa after the enactment of Law Number 11 of 2020 concerning Job Creation. Based on this, the author formulates the problem, namely: first: What are the implications of the establishment of BUM Desa which was established after Law Number 11 of 2020 concerning Job Creation. Second: What are the problems with BUM Desa after the promulgation of Law Number 11 of 2020 concerning Job Creation. This legal research is a combination of empirical normative research, the research was carried out by reviewing and examining secondary data first which was then continued with primary data obtained by interviews. The results of this research conclude that BUM Desa obtains Legal Entity status when an electronic registration is issued by the minister who handles government affairs in the field of Law and Human Rights which is integrated into the legal entity administration system. However, due to the long registration process in the Village Ministry System, BUM Desa has not been able to carry out collaborative activities on a legal basis because it is not yet legal as a legal entity.